Pulmonary infections in patients with myelodysplastic syndromes receiving frontline azacytidine treatment. Issue 2 (23rd January 2020) - Latagliata, Roberto; Niscola, Pasquale; Fianchi, Luana; Aloe Spiriti, Maria Antonietta; Maurillo, Luca; Carmosino, Ida; Cesini, Laura; Sarlo, Chiara; Piccioni, Annalina; Campagna, Alessia; De Luca, Maria Lucia; De Benedittis, Daniela; et al.
Abstract: Pulmonary infections (PIs) are a major complication of patients with myelodysplastic syndromes (MDS). We retrospectively evaluated 234 MDS patients treated with azacytidine (AZA). The total number of AZA cycles was 2886 (median 8 cycles per patient). There were 111 episodes of PI (3.8% of AZA cycles) in 81 patients (34.6%). PIs were considered of fungal origin in 27 cases (24.3%), associated to bacteremia in 11 cases (9.9%), to influenza infection in two cases (1.8%) and of unknown origin in the remaining 71 cases (64.0%). Forty‐five PI episodes were documented in cycles 1 to 4 of AZA (5.1% of 875 cycles) and the remaining 66 episodes beyond the fourth cycle (3.2% of 2011 cycles) ( P = .017). Overall, a fungal PI was documented in 13/875 (1.5%) cycles 1 to 4 and in 13/2011 (0.6%) cycles beyond the fourth cycle ( P = .001). A baseline chronic pulmonary disease was significantly associated to a higher risk of severe PIs. In the survival analysis, cases of PI in patients who progressed to acute leukemia (PAL) were excluded, in view of the predominant influence of PAL on the outcome of the patients. A PI unrelated to PAL documented during the first 4 AZA cycles was an independent factor predicting lower survival (OR, 2.13; 95% CI, 1.37‐3.33; P = .001). In conclusion, PIs are common in MDS patients receiving AZA, in particular during the first cycles of treatment and are associated with an unfavorable outcome. The results of our study raise the issue of the need of a tailored infection prevention strategy.